Mesoproterozoic UHT metamorphism in the Southern Irumide Belt, Chipata, Zambia: Petrology and in situ monazite dating - Karmakar, Shreya; Schenk, Volker (Precambrian research, 2016)
The Irumide Belt sensu lato of eastern Zambia situated between the Bangweulu Block and the Zimbabwe Craton is one of the Mesoproterozoic belts in southern Africa, which developed during the formation of the supercontinent Rodinia. Though in several of these belts the orogenic evolution seems to be connected to a long lasting high temperature history (∼200Ma), the duration and geodynamic causes of the metamorphism in this particular belt have not been studied. Here we report the results of an integrated petrological study and texturally controlled in situ monazite dating of spinel-quartz and orthopyroxene-cordierite granulites and associated charnockites and mafic rocks from the Chipata Terrane of the Southern Irumide Belt (SIB), which revealed a single stage high to ultra-high temperature (HT, UHT) metamorphism during the Mesoproterozoic Irumide orogeny. The earliest textural relicts of the prograde evolution are patchy sillimanite aggregates interpreted to represent pseudomorphs after andalusite. Sillimanite inclusions in garnet indicate garnet growth in the sillimanite stability field. During peak metamorphism garnet+sillimanite reacted to form spinel+quartz. In associated garnet-orthopyroxene-cordierite granulites, peak orthopyroxene has high Al2O3 contents of up to 7.9wt%. These peak metamorphic features point to UHT conditions of 900-1000°C (UHT) at ∼5-6kbar, in agreement with the occurrence of inverted pigeonite in associated charnockites. Orthopyroxene+cordierite coronas around prograde garnet in the second assemblage indicates decompression at UHT conditions after peak metamorphism. Subsequent isobaric cooling (IBC) led to reversal of mineral reactions and thus to replacement of spinel+quartz by garnet 2+sillimanite 2+cordierite. The IBC at still high pressures is also indicated by the formation of garnet and clinopyroxene coronas between orthopyroxene and plagioclase in associated mafic rocks. During late-stage retrogression the formation of kyanite+chlorite+quartz±staurolite±magnesite at the expense of cordierite and garnet in garnet-cordierite-sillimanite gneiss indicates prevailing high pressures (>4-5kbar) during cooling below temperatures of ∼550°C. Monazite grains occurring in different textural settings (inclusions in garnet, and in matrix) revealed ages between 1031±4 and 1013±4Ma for the peak HT to UHT metamorphism of the Chipata terrane of the SIB. The metamorphism is almost synchronous with the age of intracrustal melting in the northern Irumide Belt (IB; 1020-950Ma) and slightly younger than the age of continental margin arc magmatism in the SIB (∼1090-1040Ma). The metamorphism therefore most likely occurred as a consequence of subduction related magmatism and the collision between the IB (margin of the Bangweulu block) and the SIB (margin of an unknown southern craton) during the Mesoproterozoic Irumide orogeny.